Elaboration of Transactional Conversation for Middle-School Students: Speaking Skills Through "COIN-SPA" Learning - Hendrowati, Heny; Fatmasari, Elly; Iskandar, Iskandar (ETDC: Indonesian Journal of Research and Educational Review, 2023)
COIN-SPA learning is one of the learning models that will be used in this research to improve speaking skills in transactional conversations. Considering that the speaking skills of class VII-A students at SMP Negeri 1 Pati are not yet optimal due to the poor learning process and the low level of student activity in practicing speaking in English, it is necessary to have learning that can create opportunities for students to do more practice, speaking, namely COIN-SPA learning. This research aims to: (a) determine the implementation of the transactional conversation learning process; (b) increase student activity; and (c) improve speaking skills in transactional conversation through COIN-SPA learning for class VII-A students of SMP Negeri 1 Pati, which was carried out in two cycles with a time allocation of 6 x 40 minutes each (three meetings). The results of the research show that the implementation of the transactional conversation learning process with COIN-SPA learning can be carried out with category C (fair) in cycle I and increased to category B (good) in cycle II. The results of observations of student activities showed an increase in the average percentage from 59.9% to 78.4% or a percentage gain of 18.5%. The results of observing learning outcomes showed an increase in the average score from 73.68 to 76.44 or an increase of 2.76, and further increasing to 78.55, or an increase of 2.11, in the last cycle. Based on these results, it can be concluded that COIN-SPA learning has gone well so that it can be used to improve speaking skills in transactional conversations, and through COIN-SPA learning, it can increase student activity and student learning outcomes in transactional conversation learning in class VII-A SMP Negeri 1 Pati.